2022
DOI: 10.21608/tsnj.2022.221557
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adoption of positive coping strategies on women's knowledge and practices related to endometriosis

Abstract: Background and Aim: Endometriosis affects 5 to 15% of women in their reproductive years. It causes a wide range of social, psychological, and emotional issues. The study aimed to evaluate effectiveness of adoption of positive coping strategies on women's knowledge and practices related to endometriosis. Subjects and Methods: This study used quasi-experimental research design. The research was carried out in Egypt at the endoscopy section of Zagazig University Hospital and Al Ahrar Hospital. A purposive sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Table 1, Number of participants (%) of Demographic Characteristics, Most of the ages were between (16 -25 Years) 1353(73.5 %), most Education Levels (University) 1357(73.8 %), and Marital Situation the most were (Single) 1467(79.7 %). 3, The Correlations between Knowledge and Education Levels, the p-value > 0.05 means there is no relationship between education level and knowledge of endometriosis, This study agree with many previous study as [12], [4], [8], [10], [12], [13], [23], [2], [1], [21], [22], [11], [20], [18], [10], [16], [24], [14], [25], [3], [4], [6], [7], [8], [10].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Table 1, Number of participants (%) of Demographic Characteristics, Most of the ages were between (16 -25 Years) 1353(73.5 %), most Education Levels (University) 1357(73.8 %), and Marital Situation the most were (Single) 1467(79.7 %). 3, The Correlations between Knowledge and Education Levels, the p-value > 0.05 means there is no relationship between education level and knowledge of endometriosis, This study agree with many previous study as [12], [4], [8], [10], [12], [13], [23], [2], [1], [21], [22], [11], [20], [18], [10], [16], [24], [14], [25], [3], [4], [6], [7], [8], [10].…”
Section: Resultssupporting
confidence: 87%
“…Since the search for a non-invasive diagnostic endometriosis marker has been conducted for many years without success so far, it seems that awareness of the clinical presentation and reported symptoms may help to provide earlier diagnoses. [12], the outcome is important, given that stronger awareness, acknowledgement, and education about endometriosis among the general public have been coined the "bedrock of an improved response" [13], Although endometriosis affects an estimated 176 million women worldwide, it has been wrongly reported that endometriosis is a rare condition among African women, mainly due to lack of awareness among healthcare providers and historical bias [14], Adoption of Positive coping strategies had a significant effect on women's knowledge, practices related to endometriosis. [15], Knowledge and attitudes to counsel endometriosis patients on fertility issues and fertility preservation options should be included in the training curricula of gynecologists.…”
Section: Introductionmentioning
confidence: 99%
“…3, The Correlations between Knowledge and Education Levels, the p-value > 0.05 means there is no relationship between education level and knowledge of endometriosis, This study agree with many previous study as (Kotowska et al, 2021), (Adewunmi & Sasah, 2022. ), (Arab et al, 2022), (Henry et al, 2022), (Kotowska et al, 2021), (Le Busque & Mellish, 2023), (S. L. Mohamed El Sayed et al, 2022), (Ramani Devi et al, 2021, (Roullier et al, 2021), (Szymańska & Dąbrowska-Galas, 2021), (Wróbel et al, 2022), (Khan et al, 2022), (Sodeinde & Konu, 2022), (Randhawa et al, 2021), (Henry et al, 2022), (Navarria-Forney et al, 2020), (Mohamed & Hassan, 2020. ), (Mecha et al, 2022), (Eldardery et al, 2022), (Abd Elrahim et al, 2022), (Adewunmi & Sasah, 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Although endometriosis affects an estimated 176 million women worldwide, it has been wrongly reported that endometriosis is a rare condition among African women, mainly due to lack of awareness among healthcare providers and historical bias (Mecha et al, 2022), Adoption of Positive coping strategies had a significant effect on women's knowledge, practices related to endometriosis.(S. Mohamed El Sayed et al, 2022), Knowledge and attitudes to counsel endometriosis patients on fertility issues and fertility preservation options should be included in the training curricula of gynecologists. (Navarria-Forney et al, 2020), Women with endometriosis experience that they are treated with ignorance regarding endometriosis in nonspecialized care.…”
Section: Introductionmentioning
confidence: 99%